2013
DOI: 10.1128/jcm.01373-13
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Liquid Medium (M7H9C) for Routine Culture of Mycobacterium avium subsp. paratuberculosis To Replace Modified Bactec 12B Medium

Abstract: Liquid culture of Mycobacterium avium subsp. paratuberculosis from clinical samples, such as feces, is the most sensitive antemortem test for the diagnosis of Johne's disease in ruminants. In Australia, New Zealand, the United States, and some other countries, the Bactec 460 system with modified Bactec 12B medium (Becton, Dickinson) has been the most commonly used liquid culture system, but it was discontinued in 2012. In this study, a new liquid culture medium, M7H9C, was developed. It consists of a Middlebro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
47
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 42 publications
0
47
0
5
Order By: Relevance
“…A notable validation of NlpC/P60 proteins as antibiotic targets has been done for M. marinum IipA (homolog of MAP_1203), where the gene knockout was constructed and complemented to show a lack of growth and infectivity in macrophages. 13 Since MAP is resistant to many antibiotics, 28,29 novel approaches must be explored in treating infections by this organism. Furthermore, since NlpC/P60 proteins are found in all Eubacteria, any compounds that are capable of inhibiting these enzymes have the potential to be developed into Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…A notable validation of NlpC/P60 proteins as antibiotic targets has been done for M. marinum IipA (homolog of MAP_1203), where the gene knockout was constructed and complemented to show a lack of growth and infectivity in macrophages. 13 Since MAP is resistant to many antibiotics, 28,29 novel approaches must be explored in treating infections by this organism. Furthermore, since NlpC/P60 proteins are found in all Eubacteria, any compounds that are capable of inhibiting these enzymes have the potential to be developed into Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…M7H9C liquid culture medium for MAP containing Middlebrook 7H9 broth base (Becton Dickinson [BD]), PANTA antibiotic preparation (BD), mycobactin J (Allied Monitor), Middlebrook ADC enrichment (containing bovine albumin fraction V, dextrose, and catalase; BD), and egg yolk was prepared and cultures were performed as previously described (4). Modified Bactec 12B medium (Becton Dickinson) containing egg yolk, PANTA Plus, and mycobactin J was prepared as described previously (7).…”
Section: Methodsmentioning
confidence: 99%
“…For MAP, liquid culture media, such as Bactec 12B medium, have been found to be more sensitive than solid culture media, such as Herrold's egg yolk medium (HEYM) supplemented with mycobactin J (4)(5)(6). MAP in cultures with positive growth is confirmed by the demonstration of mycobactin dependency or directly by molecular techniques (7).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…The purpose of adding egg yolk to culture media used for MAP is still unclear, but neutralization of the chemical decontaminant HPC seems to be a common reason (Whittington 2010). Whittington et al (2013) subsequently suggested that egg yolk provides major carbon and energy sources as well as the surfactant lecithin. The question arises, are sub-lethally injured MAP cells likely to benefit from, or be adversely affected by, such a rich source of nutrients when trying to repair heat or dessication damage?…”
mentioning
confidence: 99%